Spray-Dried Griseofulvin-Lactose Matrix for Enhanced Solubility Using a Spray-Drying Biochemical Process - Tian Lan; Jie Yang; Zhi-jie Yang; Hong-wen Wu (Journal of Chemistry)
Griseofulvin (GF) is a hydrophobic drug with a low solubility. In order to improve the solubility of GF, which has low water solubility, this report uses the spray-drying technique to prepare complexes with lactose to promote the solubility and oral bioavailability of GF. The solution samples were spray dried using different ratios of ethanol or acetone solutions as dissolution media. By characterization of the obtained spray-dried powders, we found that the solubility of the different groups of samples obtained by spray drying was increased, and similarly, their dissolution rates were also increased to different degrees. By comparison, the greatest increase in solubility was obtained in an aqueous acetone solution, showing the greatest ability and efficiency of acetone in promoting the solubility of GF during the spray-drying process.